Pengaruh Interaksi Guru dan Murid terhadap Hasil Belajar Murid dalam Pembelajaran Matematik di MAN 1 Medan - Sulthon Zulkarnain Siregar; Putri Nabila Lubis; Lutfia Humayra (Universitas Muhammadiyah Enrekang, 2022)
Education is a learning activity carried out by a student with the aim that the nation's children become intelligent and also develop into complete human beings. So there are many things that become the determining factor in the success of an education, one of which is the teacher-student interaction. The teacher as a teacher is a determining basis in the formation of students to achieve the goals of education itself. Therefore the interaction that is given to students greatly influences the process of the education process. It is clear that the interaction between the teacher (teacher) and those who respond (students) is a determining factor in the success of learning. Which means that the interaction relationship will form an atmosphere or classroom climate that will support the success of learning. The atmosphere is in the form of a positive and negative atmosphere, if a positive atmosphere is created then learning will be comfortable for students. A negative atmosphere is an unfavorable atmosphere that exists during the teacher-student interaction process which will cause discomfort felt by students because the teacher only focuses on providing material and ignores student motivation and also pays attention to students which causes reduced student interest in the learning process. It is because of the problems mentioned above that we take the title of our research, so that we know how big the influence of this interaction is in determining student mathematics learning outcomes.